Activation of Hippocampal Microglia Mediates Chronic Stress-induced Depression-like Behavior in Rats with Ischemic Stroke - TAO Xi; YANG Chen; TANG Wenjing; WU Siyuan; DENG Jinggui (康复学报)
ObjectiveTo explore the role of hippocampal microglia activation and related proinflammatory factors in depression-like behavior induced by chronic stress in rats with ischemic stroke.MethodsA total of seventy-five healthy male Sprague-Dawley rats were used to establish a right middle cerebral artery occlusion (MCAO) model with 70 min ischemia. One week after MCAO, rats were assigned to stroke and "stroke + stress" groups according to the SPSS random number generator. And according to time course, the former was divided into 1-week stroke, 2-week stroke and 4-week stroke groups, while the latter was divided into "2-week stroke + 1-week stress" (referred to as "1-week stress") and "4-week stroke + 3-week stress" (as "3-week stress") groups, with 15 rats in each group. "Chronic unpredictable mild stress plus isolation" was used in the stress group. The body weight, open field test (OFT), novelty-suppressed feeding test (NSFT) and sugar preference index (SPI) of rats were evaluated at each time point. Residual brain volume ratio was detected by TTC staining. The expression of Iba-1, IL-1β and IL-18 in the affected hippocampus was detected by Western blot. The fluorescencs intensity of Iba-1 in the CA1 region of the affected hippocampus was detected by immunofluorescence staining.ResultsTwo weeks after MCAO, compared with the 2-week stroke group, the body weight and counts of rearing and grid crossing of OFT decreased in the 1-week stress group (all P<0.05). Four weeks after MCAO, compared with the 4-week stroke group, decreases in the body weight, SPI and counts of rearing and grid crossing of OFT, and extended latency and reduced food intake of NSFT were observed in the 3-week stress group (all P<0.05). TTC staining showed different degrees of atrophy of corpus callosum and striatum in each group, but the ratio of residual brain volume was not statistically different (P>0.05). Western blot showed that, compared with the 4-week stroke group or 1-week stress group, the expression of Iba-1, IL-1β and IL-18 in the affected hippocampus was significantly higher in the 3-week stress group (all P<0.05). The expression of Iba-1, IL-1β or IL-18 in affected hippocampus of the stroke group was significantly different at 3 different time points (all P<0.05). Immunofluorescence staining showed that, compared with the 4-week stroke group or 1-week stress group, the fluorescence intensity of Iba-1 in the CA1 region of affected hippocampal was significantly higher in the 3-week stress group (all P<0.05). The fluorescence intensity of Iba-1 in the CA1 region of the stroke group was significantly different at 3 different time points (all P<0.05).ConclusionChronic stress-induced depression-like behavior in ischemic stroke rats is not only related to the activation of affected hippocampal microglia and the release of related proinflammatory factors, but also may be time-dependent. Inflammatory response in the affected hippocampus after stroke may be a continuous process.